Management of ledge and overprepared access cavity in mandibular second molar - Steward Hadi; Widyastuti, Wiena; Dina Ratnasari (Conservative Dentistry Journal, 2025)
Background: Endodontic success depends on precise execution. Iatrogenic complications such as ledge formation and excessive access cavity preparation can obstruct canal negotiation, impair disinfection, weaken tooth structure, and increase treatment failure. Purpose: This case report describes the management of a ledge and an overprepared access cavity in a mandibular second molar. Case: A 33-year-old female was referred with tooth 37 restored using a subgingival temporary filling. Radiographs revealed mesial radiolucency, an excessively extended access cavity, and a ledge in the mesial root canal. Case Management: Treatment was performed under rubber dam isolation. Temporary restoration and caries were removed, followed by artificial wall construction with resin composite. Pre-curved K-files (#10, #15) were used to bypass the ledge and establish a glide path and determine the working length. Rotary glide path instruments and heat-treated NiTi files were used to shape up to size #25/.04, with irrigation using 5.25% NaOCl and 17% EDTA. After intracanal calcium hydroxide medication, obturation was completed using bioceramic sealer, warm vertical compaction in the mesial root, and a single-cone technique in the distal root. A flowable bulk-fill composite was placed as the intracanal barrier, and final restoration was completed with packable composite. Conclusion: Ledges obstruct instrumentation and disinfection, requiring flexible pre-curved files and careful negotiation to re-establish canal patency. Excessive access cavity preparation compromises peri-cervical dentin, increasing susceptibility to structural failure. Bulk-fill flowable composite offers good marginal adaptation and may improve restoration durability. Thorough planning, controlled instrumentation, and appropriate restorative materials are essential to manage such complications effectively.